Analisys of Lead Content in Rice Snail from Taliwang Lake - Khairuddin, Khairuddin; Yamin, M. (Jurnal Biologi Tropis, 2025)
The aim of the study was to determine the content of Lead (Pb) in the Rice Field Snail (Pila ampullacea) from Taliwang Lake. The special benefit is to protect consumers who consume Snail from Pb contaminant. The research was conducted in water body of Taliwang Lake. The Eastern and western parts of the lake were taken to be 2 research stations. Small nets and tweezers are used to sample 20 snails for each station. Furthermore, each snail sample was put into a plastic bag and then stored in a sample box. The research sample was then analyzed at the Environmental Laboratory Center for the West Nusa Tenggara Environment and Forestry Office. The method of data analysis was carried out by taking muscle tissue from snails and then analyzing the content of Pb heavy metals by using an Atomic Absorption Spectrophotometer. Lead concentrations in snail tissue were measured after adding concentrated Na2SO4 and CuSO4, which were heated at 350ºC for 2-3 hours until the solution was clear. The conclusion of this study is that the content of Pb in Rice field snails (Pila ampullacea) was 0.01 ppm.